Two close binaries across the hydrogen-burning limit in the Praesepe open cluster. Issue 3 (21st August 2020) - Lodieu, N; del Burgo, C; Manjavacas, E; Zapatero Osorio, M R; Alvarez, C; Béjar, V J S; Boudreault, S; Lyke, J; Rebolo, R; Chinchilla, P
ABSTRACT: We present Keck I/OSIRIS and Keck II/NIRC2 adaptive optics imaging of two member candidates of the Praesepe stellar cluster ( d   =  186.18 ± 0.11 pc; 590–790 Myr), UGCS J08451066+2148171 (L1.5 ± 0.5) and UGCS J08301935+2003293 (no spectroscopic classification). We resolved UGCS J08451066+2148171 into a binary system in the near-infrared, with a K -band wavelength flux ratio of 0.89 ± 0.04 and a projected separation of 60.3 ± 1.3 mas (11.2 ± 0.7 au; 1σ). We also resolved UGCS J08301935+2003293 into a binary system with a flux ratio of 0.46 ± 0.03 and a separation of 62.5 ± 0.9 mas. Assuming zero eccentricity, we estimate minimum orbital periods of ∼100 yr for both systems. According to theoretical evolutionary models, we derive masses in the range of 0.074–0.078 and 0.072–0.076 M⊙ for the primary and secondary of UGCS J08451066+2148171 for an age of 700 ± 100 Myr. In the case of UGCS J08301935+2003293, the primary is a low-mass star at the stellar/substellar boundary (0.070–0.078 M⊙ ), while the companion candidate might be a brown dwarf (0.051–0.065 M⊙ ). These are the first two binaries composed of L dwarfs in Praesepe. They are benchmark systems to derive the location of the substellar limit at the age and metallicity of Praesepe, determine the age of the cluster based on the lithium depletion boundary test, derive dynamical masses, and improve low-mass stellar and substellar evolutionary models at a well-known age and metallicity.